2022
DOI: 10.30595/hmj.v5i2.12744
|View full text |Cite
|
Sign up to set email alerts
|

Analisis <i>In Silico</i> Senyawa Aktif Batang Kayu Bajakah (<i>Spatholobus littoralis</i> Hassk) Sebagai Terapi Psoriasis

Abstract: Background :  Innovative topical psoriasis therapy continues to be developed, Spatholobus littoralis Hassk or Bajakah has antipsoriatic activity so can be used as a topical herbal medicine in reducing the severity of psoriasis. In silico is a computational experiment which is analogous to biological experiments in vivo and in vitro. Objective : To evaluate content of Spatholobus littoralis Hassk using in silico analysis in the treatment of psoriasis. Methods : The active compound Spatholobus littoralis Hassk e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…as a psoriasis therapy. This shows the potential of bajakah as an effective traditional medicine for the treatment of skin diseases [38]. Based on the results of this in silico analysis, the study concluded that bajakah wood (Spatholobus littoralis Hassk.)…”
Section: Pharmacological Activity Of Bajakahmentioning
confidence: 79%
See 2 more Smart Citations
“…as a psoriasis therapy. This shows the potential of bajakah as an effective traditional medicine for the treatment of skin diseases [38]. Based on the results of this in silico analysis, the study concluded that bajakah wood (Spatholobus littoralis Hassk.)…”
Section: Pharmacological Activity Of Bajakahmentioning
confidence: 79%
“…Although there are limitations to thorough scientific research on bajakah, some early research points to the potential of this plant in traditional medicine. One study showed that bajakah was also found to have potential as a topical herbal remedy that can reduce the severity of psoriasis, a skin condition characterized by red, itchy, and scaly skin [24]. Bajakah extract has shown anti-inflammatory activity and inhibited the excessive proliferation of skin cells in psoriasis.…”
Section: Biodiversity Morphological and Traditional Use Of Bajakahmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in accordance with research that has been done before. 17 Triterpenoids which are known to have a role as high antioxidant active compounds are aligned with research on Spatholobus littoralis Hassk. stem extract is proven to accelerate fibroblast migration and as an anti-inflammatory agent in the wound healing process.…”
Section: Resultsmentioning
confidence: 99%